Innovations in Maternal and Child Health Services in Remote Areas: An Effective Strategy to Reduce Infant Mortality - Maulidanita, Riska; Annur Hanya, Rizca; Endrianto, Endrixs; Sulfianti (Oshada, 2025)
Infant mortality rates remain a serious public health issue, particularly in remote areas of Indonesia that face limitations in terms of facilities, infrastructure, and resources. This situation is exacerbated by difficult access to transportation, a shortage of health workers, and low levels of health literacy among the population. This article aims to examine various innovations in maternal and child health services that can contribute to reducing the IMR in remote areas. The method used is a literature review of recent studies discussing the implementation of innovative strategies, including the use of digital technology, strengthening the role of local healthcare workers, and community involvement in health programs. The findings indicate that the implementation of telemedicine, enhancing the capacity of village midwives, providing emergency transportation, and community-based health education have proven effective in improving access to and the quality of healthcare services. These findings underscore that innovative strategies tailored to local social and cultural conditions hold significant potential for sustainably reducing infant mortality rates in remote areas.